Final Survey for the Impact Evaluation of School Based Management in Sri Lanka - National Education Research and Evaluation Centre, University of Colombo (University of Colombo, 2012)
Final Survey for the Impact Evaluation of School Based Management in Sri Lanka Study on Inclusive Education in Sri Lanka In the present study the definition of Inclusive Education used was Bristol Local Authority’s Equalities and Educational Inclusion Policy and Framework’ definition: “Educational inclusion is about equal opportunities for all learners, whatever their age, gender, ethnic origin, religious belief, care status, impairment, sexuality, attainment or social or economic background. It pays particular attention to the provision made for, and the achievement of, different groups of learners”. The study attempted 1. To examine the extent to which the policy on Inclusive Education has been formulated formally in Sri Lanka, 2. To assess the level of awareness of Inclusive Education among relevant stakeholders such as educational administrators, principals, teachers, parents and students, 3. To examine the extent to which an Inclusive Culture has been created in schools in the sample, 4. To evaluate the extent to which Inclusive Education has been implemented in the selected schools in the sample, 5. To identify the problems and issues faced in implementing Inclusive Education in Sri Lankan schools, and 6. Make recommendations for effective implementation of Inclusive education in the country. Formulation of Inclusive Education Policy in Sri Lanka: The impressive achievements in extending access to education in Sri Lanka are indisputably the cumulative result of progressive measures taken even prior to regaining independence. In 1997 compulsory education regulations for the 5 – 14 age group and proposals for the establishment of a well-equipped quality school in each of the 324 local administrative divisions to ensure on equitable distribution of educational opportunities were approved. Further, Educational Reforms of 1997 support the philosophy and practice of inclusive education in Sri Lanka. However, concern is expressed regarding the children, though relatively small in number, still bereft of access to schools, who drop out of schools early and whose learning achievement is low. It is even more disquietening that most of these ‘un-reached or excluded’ children are from poor and low socio-economic backgrounds, in displaced or conflict-affected communities, the plantation sector, girls in certain communities and children with disabilities. Experience of other countries such as Canada, United Kingdom, USA and Australia, indicate that the formulation of an Inclusive Education Policy is an essential condition for implementation of Inclusive Education. In Sri Lanka, however, in spite of a declared policy of Inclusive Education, while efforts are being taken to extend access to children who do not enroll in school and to retain and improve the learning achievement of marginalized groups, there is little evidence of children with disabilities being mainstreamed in formal school. The National Policy on Disability has formulated a far-reaching set of recommendations which could have contributed to the subsequent implementation of Inclusive Education. These recommendations need to be considered seriously and accepted by the policy making body in education, National Education Commission, which does not appear to have materialized so far. Level of Awareness on Inclusive Education among Relevant Stakeholders: Implementation of Inclusive Education rests largely on the awareness on Inclusive Education among stakeholders. The analysis of data indicated that (1) Zonal Directors had stated that they had a high or a moderate awareness of aspects related to Inclusive Education, (2) the level of awareness of the officers in the Zonal offices was adequate as stated by the Zonal Directors, (3) the majority of In-service Advisers had affirmed that they had sufficient awareness of most aspects but not on Special Education, (4) the predominant majority of principals were aware of all aspects impinging on Inclusive Education, (5) the awareness of Sectional Heads on aspects such as Convention on the Rights of the Child and compulsory education was high but not on Education for All and Equal Educational opportunity, and (6) the awareness of teachers on most aspects (similar to the Sectional Heads) was satisfactory but not on Inclusive Education. However, the majority of teachers thought Special Education was the same as Inclusive Education. Awareness of education as a right of children of almost half of the parents was very poor and of another 46.5% was poor. More than 50% of the student stated that they knew that education was right which they should be assured of. Creation of an Inclusive Culture in Schools in the Sample: The study indicated that relevant training which focused on areas of Special Education, Child Rights and Inclusive Education had been conducted for teachers in order to prepare them for developing an Inclusive Culture in schools. The responses of the principals though, showed that the ambiguity and contradiction regarding the term Inclusive Education as well as uncertainty in their commitment to achieve Inclusive Education. In-Service Advisers perceived implementation of Inclusive education as quite feasible though training on special education, inclusive education and child-friendly school had reached only a minority. The retention of a category of In-Service Advisers in Inclusive/Special Education too confirmed that the principle of mainstreaming had not yet been accepted. It was commendable that the majority of the respondents saw an Inclusive Culture being created in their schools. Extent of Implementation of Inclusive Education: There was overwhelming confirmation from the teachers that an inclusive education practice has been created in schools though community participation in Inclusive Education in schools was less evident. A majority of them were happy at school, mainly because of good school management and the conducive environment. Primary and secondary Sectional Heads, In-service Advisers and the Zonal Directors also echoed similar sentiments. The overall perception of parents regarding inclusive education in their children’s schools was also extremely positive. Almost two-thirds of the principals disagree that the presence of special education needs children affects school management and that inclusive education obstructs the education of normal children but almost half disagree that presence of slow learners ‘has not been a barrier’ to the creation of a child-friendly environment. Finally, the most important of the evaluators of successful of implementation of Inclusive Education, the students had positive perceptions of implementation of inclusive education in their schools but around 10% had experienced certain types of harassment. Students’ responses reiterated the important role played by the teacher in implementing Inclusive Education. Student responses can be accepted as valid indicators of an objective evaluation. Teachers appear to have developed sensitivity and responsiveness towards students. However, whether teachers enable rather than disable students has not been probed or proven. Responding to Children at Risk of Exclusion: The identification of slow learners appears to be only on the basis of class assessment and makes no reference to the Standard Assessment carried out on entry to school against which improvements in learning achievement of individual children could have been made. Similarly while school authorities spoke about action taken to resolve issues faced by groups of children who need more attention and which they felt were effective, effectiveness of such measures are not considered in relation to learning achievement or participation or inclusion of special groups of children. However the responses fail to give us information on the actual degree of inclusion of children with special needs in formal school. Of the students who were having problems related to their studies identified poverty and socio-economic status as the main barriers. The home factor was considered by the teachers (50.7%), Sectional Heads (81.4%) and the Zonal Directors (34.8%) also as the main barrier. Neither the students nor teachers considered that the school factor was responsible for their slow learning. Yet the Zonal Directors attributed 63.6% of the responsibility for slow learning to school factors. While 21.7% of the students felt the war had resulted in slow learning, ‘war’ was mentioned by only 3 out of a total of 643 educational personnel as leading to slow learning. Teachers, Sectional Heads, principals and Zonal Directors all listed various measures they had used to improve learning achievement of slow learners and to address the needs of children with disabilities. These included Making parents aware, Providing additional and medical assistance, Counseling programmes, Educational facilities and requirements, A caring & loving atmosphere, Special teaching methodologies, Rewarding the attendance, Supervision, Disaster management programmes, Supplementary practical activities and Creating better security. They targeted the special individual students or groups who needed support. In implementing these measures, the education personnel had obtained assistance from various groups such as the School Development Society and the Past Pupils’ Association, the Medical Officers, Child protection & Probation Officers, Public Health Inspectors, Public Health Nurses, Religious leaders and Police Officers, as was relevant. All the above respondents claimed that these measures had been effective and had achieved the expected goals. It is noteworthy, that except for one statement, for the others, more than 90% of the students had not responded at all. Almost a quarter, 22.9% of the students had said that the teachers do not appreciate their special talents and 9.5% had said that teachers do not help them to overcome weaknesses. Obviously the schools had still to go much further to achieve the objectives of Inclusive Education. Problems and Issues in Inclusive Education and the Suggestions Made by Stakeholders to Address them: The principals identified some threats, for example, shops selling cigarettes and liquor, which could have an impact on students’ learning achievement, and led to their engaging in vice and deviant behaviour. In addition residence in vulnerable locations, such as refugee camps, violent or vice-ridden, or being affected by Tsunami were also listed. The factors identified as associated with slow learning and children with special needs were (1) lack of human and physical resources, (2) poor attendance by principals, teachers, and in-service advisers and (3) negative attitudes, by principals and teachers. Two other factors given by ISAs was ‘Difficulties in reading & writing/Communication difficulties’ and Mental stress/Restlessness/Desire for seclusion. All groups of respondents (Principals, teachers, parents, ISAs & Zonal Directors) were united in stressing the need for increasing the awareness while training of trainers/teachers was suggested by teachers, ISAs & Zonal Directors and creating a pleasant teaching-learning environment/Remedial teaching by principals, teachers, ISAs. Principals and teachers suggested the need for supervision & management, provision & fair distribution of resources, while parents, teachers and Zonal Directors suggested the need for policies and actions, student development and Special education. The very critical areas of engaging in co curricular activities, curriculum development, and providing equal opportunities and setting an inclusive education date were mentioned only by the Zonal Directors. ISAs stressed the need for improving literacy Recommendations: The following recommendations (which includes some of the recommendarions made in the National Disability Policy) are submitted 1. Taking cognizance of the role of National Education Commission as the policy-making body in Sri Lanka, it is imperative that the Commission formulates a National Policy on Inclusive Education giving due care and attention to, how Inclusive Education is defined, and national policies on Inclusive Education have been formulated in other parts of the world. Especially important is the need to remove any ambiguity and contradictions when formulating this policy. 2. In order to avoid a formulated policy of Inclusive Education from being becoming a dead letter, the NEC should develop an Action Plan for its implementation, for which due consideration can be given for the work already completed in 2003-04. The Provincial and Zonal authorities should be sensitized regarding this policy, especially about the need for resource mobilization and allocation required for effective implementation. 3. Standard Assessment Records should be maintained for all children when they enter school and careful assessment and recording of periodical assessments should be done, so that growth and progress of all children, disabled or not, can be maintained, and when detected as needing special assistance, such assistance could be offered. 4. In making these Assessments, it is necessary that teachers, parents and medical practitioners (if necessary) should collaborate. 5. All teacher development programmes (primary and secondary and university and NCOE) should include a course on Inclusive Education which should be mandatory for all teachers to follow so that awareness about Inclusive Education can be developed systematically in the school system and not on an ad hoc basis. The incorporation of Inclusive Education into the relevant subjects such as Methods of Teaching, Sociology of Education, Educational Psychology, Counselling and Guidance and Educational management, in the teacher education curriculum would be the best strategy. 6. NIE and the Universities, especially the Department of Special Needs Education, Open University should take the lead in deciding on whether curriculum adaptation and diversified instruction is necessary and if so to recommend the needed changes and develop appropriate teacher education materials to be used by the teachers. 7. The role of the special education teacher needs to change to become a facilitator for the entire school. The setting up of a teacher support team in every school can be promoted to provide on-site support as a matter of policy. 8. Non-discriminative social relationships in the school environment should be promoted so that all children who are normally excluded can be welcomed and accepted into schools and support networks for such children can be built up. 9. At school level, more informal core-team training should be made so that there is more involvement of parents and community members in acquiring knowledge and skills. 10. Needed resources should be identified (this can be done at the time the needs and priorities are identified for the Education Sector Development Programme Framework) for all schools so that needed resource allocations can be budgeted for made available, without delay. 11. Quality Inputs given to schools should include those inputs that make the school accessible to all children, including classrooms, playgrounds, toilets, and other equipment and facilities. 12. Where residential accommodation is available in schools, priority should be given to children who have disability. 13. Linkages to be developed and strengthened between Special schools, both state and private, for mutual benefit of both and state should facilitate the entry of children from special schools to the mainstream. 14. Community-based rehabilitation programmes should be strengthened so that support in the form of promoting access to inclusive education, introducing reforms in schools, and providing supporting materials is facilitated. 15. Wide publicity to be given to the changes recommended in policy. For this purpose, collaboration from the educational institutions such as the NIE, authorities such as the Provincial Ministries and Zonal Departments of Education and the media should be mobilized.